Post-resuscitation myocardial dysfunction in out-of-hospital cardiac arrest patients randomized to immediate coronary angiography versus standard of care. (April 2020) - Elfwén, Ludvig; Lagedal, Rickard; Rubertsson, Sten; James, Stefan; Oldgren, Jonas; Olsson, Jens; Hollenberg, Jacob; Jensen, Ulf; Ringh, Mattias; Svensson, Leif; Nordberg, Per
Abstract: Background: Immediate coronary angiography with subsequent percutaneous coronary intervention (PCI) has the potential to reduce post-resuscitation myocardial dysfunction in out-of-hospital cardiac arrest (OHCA) patients. The aim of this study was to see if immediate coronary angiography, with potential PCI, in patients without ST-elevation on the ECG, influenced post-resuscitation myocardial function and cardiac biomarkers. Methods: A secondary analysis of the Direct or Subacute Coronary Angiography in Out-of-Hospital Cardiac Arrest (DISCO) trial (ClinicalTrials.gov ID: NCT02309151). Patients with bystander-witnessed OHCA, without ST-elevations on the ECG were randomly assigned to immediate coronary angiography within two hours of cardiac arrest (n = 38) versus standard-of-care with deferred angiography (n = 40). Outcome measures included left ventricle ejection fraction (LVEF) at 24 h, peak Troponin T levels, lactate clearance and NT-proBNP at 72 h. Results: In the immediate-angiography group, median LVEF at 24 h was 47% (Q1-Q3; 30–55) vs. 46% (Q1-Q3; 35–55) in the standard-of-care group. Peak Troponin-T levels during the first 24 h were 362 ng/L (Q1-Q3; 174–2020) in the immediate angiography group and 377 ng/L (Q1-Q3; 205–1078) in the standard-of-care group. NT-proBNP levels at 72 h were 931 ng/L (Q1-Q3; 396–2845) in the immediate-angiography group and 1913 ng/L (Q1-Q3; 489–3140) in the standard-of-care group. Conclusion: In this analysis of OHCA patients without ST-elevation on the ECG randomized to immediate coronary angiography or standard-of-care, no differences in post-resuscitation myocardial dysfunction parameters between the two groups were found. This finding was consistent also in patients randomized to immediate coronary angiography where PCI was performed compared to those where PCI was not performed.